Experimental investigation on shear behavior of FRP post-tensioned concrete beams without stirrups. (1st October 2021) - Peng, Fei; Xue, Weichen
Highlights: The shear behavior of FRP post-tensioned concrete beams without stirrups was investigated. The effect of the prestressing level, type of flexural reinforcement, and tendon profile on shear strength was assessed. The kinematics of the critical shear crack was tracked and recorded using DIC techniques. Arching action played a major role for the shear capacity of FRP post-tensioned beams. The shear contribution of aggregate interlock in FRP post-tensioned beams was negligible. Abstract: To investigate the shear behavior of post-tensioned concrete beams with longitudinal fiber-reinforced polymer (FRP) reinforcements and without stirrups, seven large-scale beams, with a shear span-to-effective depth ratio of approximately 3.0, were tested. The test variables included the prestressing level, type of flexural reinforcement, and tendon profile. The shear crack width and slip were tracked using digital image correlation technique. It was found that the post-tensioned concrete beams failed in shear-compression or shear-tension, while the nonprestressed concrete beam failed in diagonal tension. The post-tensioned beams designed to have approximately the same longitudinal reinforcement stiffness, exhibited similar shear strength. Draping FRP tendons resulted in an increase of 8.8% in shear cracking strength, while it had slight effect on the maximum shear strength. In this study, it was demonstrated that arching action played a major role in the shear resistance of FRP post-tensioned beams, while the contribution of aggregate interlock was negligible.